Auger effect in yellow light emitters based on InGaN–AlGaN–GaN quantum wells. (25th April 2016) - Ngo, Thi Huong; Gil, Bernard; Valvin, Pierre; Damilano, Benjamin; Lekhal, Kaddour; De Mierry, Philippe
Abstract: The Auger effect and its impact on the internal quantum efficiency (IQE) of yellow light emitters based on silicon-doped InGaN–AlGaN–GaN quantum wells are investigated by power dependence measurement and using an ABC model. Photoluminescence intensity recorded as a function of excitation power density follows a linear dependence up to a threshold P T that depends on the design of the sample. Above this threshold, the variation of the intensity becomes sublinear, which is characteristic of the onset of Auger recombination processes. After extracting the evolution of IQE with pump power from the experimental data, we use a modified ABC modeling that includes the residual n-type doping to estimate the contribution of different recombination channels. We find that the Auger effect dominates in the high-excitation regime. In addition, we find that intercalating an AlGaN-strain-compensating layer reduces not only the coefficient of nonradiative recombination rates but also reduces the onset of Auger recombination.